Metformin Effects on Metabolic Coupling and Tumor Growth in Oral Cavity Squamous Cell Carcinoma Coinjection Xenografts. (May 2018) - Tassone, Patrick; Domingo-Vidal, Marina; Whitaker-Menezes, Diana; Lin, Zhao; Roche, Megan; Tuluc, Madalina; Martinez-Outschoorn, Ubaldo; Curry, Joseph
Objective: Many aggressive head and neck cancers contain 2 metabolically coupled tumor compartments: a glycolytic stromal compartment with low caveolin-1 (CAV1) and high monocarboxylate transporter 4 (MCT4) expression and a highly proliferative carcinoma cell compartment with high MCT1. Metabolites are shuttled by MCTs from stroma to carcinoma to fuel tumor growth. We studied the effect of carcinoma-fibroblast coinjection and metformin administration on a mouse model of head and neck squamous cell carcinoma. Study Design: Xenograft head and neck squamous cell carcinoma model. Setting: Basic science laboratory. Subjects and Methods: Oral cavity carcinoma cells were injected alone or as coinjection with human fibroblasts into nude mice to generate xenograft tumors. Tumors were excised and stained with immunohistochemistry for markers of metabolic coupling and apoptosis, including MCT1, MCT4, CAV1, and TUNEL assay (terminal deoxynucleotidyl transferase nick end labeling). Strength of staining was assessed by a pathologist or computer-assisted pathology software. Metformin was administered orally to mice to test effects on immunohistochemical markers in xenografts. Results: Coinjection tumors were 2.8-fold larger ( P = .048) and had 1.4-fold stronger MCT1 staining ( P = .016) than tumors from homotypic carcinoma cell injection. Metformin decreased the size of coinjection xenograft tumors by 45% ( P = .025). Metformin reduced MCT1 staining by 28% ( P = .05) and increased carcinoma cell apoptosis 1.8-fold as marked by TUNEL assay ( P = .005). Metformin did not have a significant effect on tumor size when CAV1 knockdown fibroblasts were used in coinjection. Conclusion: Coinjection with fibroblasts increases tumor growth and metabolic coupling in oral cavity cancer xenografts. Fibroblast CAV1 expression is required for metformin to disrupt metabolic coupling and decrease xenograft size.